Environmental factors, clipping and fire: effects on cerrado (Brazilian savanna) native and invasive grasses - Musso, Carolina (2015)
The Brazilian Cerrado houses a hugely diverse biota and is considered a conservation hotspot. One of the greatest threats to the integrity of this ecosystem is introduced African grasses, which can competitively exclude native grasses and cause changes in the microclimate and other disturbances. The Cerrado is a mosaic vegetation that provides different combinations, both spatially and temporally, of conditions that can become natural stressors to the herbaceous vegetation (water, nutrient and light availability). These mosaics are reflected in differences in relationships among native and invasive species, affecting competition and creating situations (place/season) that are more, or less, susceptible to invasion. The present study aimed to identify the different biological responses of native (Aristida recurvata, Aristida setifolia, Axonopus barbigerus, Echinolaena inflexa, Gymnopogon spicatus, Paspalum gardnerianum, Paspalum stellatum, Schizachyrium microstachyum, Schizachyrium sanguineum) and invasive (Melinis minutiflora and Andropogon gayanus) grasses to variations in natural stressors and to disturbance (fire and clipping), in order to understand changes in ecosystem functioning and competition processes between the grasses, and to understand invasion dynamics in this ecosystem. The presence of invasive species proved to affect the ecosystem functioning by increasing soil feeding activity. These differences were no longer observed in the dry season or when fires were frequent, showing that water availability and fire are more detrimental to soil feeding activity than is the vegetation. Laboratory experiments showed that both drought and flood simulated scenarios damaged both species, although the invasive species performed better under all watering conditions and responded better to fertilization. Underlying mechanisms such as the efficiency of photosynthesis and antioxidant mechanisms helped to explain this behavior. The invasive species grew faster and showed less cellular damage and a healthier photosystem, reflected in higher assimilation rates under stress. These differences between the native and invasive species were reduced with clipping, especially in dry soil with no fertilization, where the native species recovered better in relation to the pre-clipping levels. Flooding was as stressful as drought, but the invasive species can bypass this issue by growing an extensive root system, especially in the better-drained soils. Fire is more detrimental than clipping, with a slower recovery, while post-fire temperatures affect the germination of both invasive and native seeds and may be an important factor influencing the persistence of a diverse biota. This approach will finally contribute to the choice of the appropriate management techniques to preserve the Cerrado’s biodiversity.